CRYOPYRIN ASSOCIATED PERIODIC SYNDROME - M. Gattorno (Вопросы современной педиатрии)
Cryopyrin associated periodic syndrome (CAPS) can be represented by various clinical variants of disease course with different severity of clinical manifestations — from mild to severe (FCAS, MWS, NOMID/CINCA). They are caused by mutations of NLRP3 gene, encoding cryopyrin. Mutations of cryopyrin gene in humans lead to excessive and accelerated production of interleukin 1b. The key role of cryopyrin in massive secretion of active form of interleukin 1b suggested the possibility of treatment aimed against this cytokine.